Balancing u-shaped assembly lines heuristically - Alf Kimms (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 2000)
While balancing straight assembly lines is a well-studied problem, the Situation where the assembly line has a U-shaped Iayout is a still emerging research field. The advantage of these lines is that workers may simply turn around to operate at two legs of the line. Hence, there is an additional degree of freedom for assigning Operations to stations. This bears the hope that U-lines are more efficient than straight lines. Since work on this NP-hard problem has mainly focused on exact algorithms, we study priority rule heuristics. We adapted 16 priority rules which have been applied to the straight line case before and examine their Performance with a computational study.
Keywords: 650; U-Lines; assembly line balancing; priority rule heuristics; Fließfertigung; Scheduling-Verfahren; Heuristik; Theorie